2014
DOI: 10.1186/1478-4491-12-58
|View full text |Cite
|
Sign up to set email alerts
|

A scenario-planning approach to human resources for health: the case of community pharmacists in Portugal

Abstract: BackgroundHealth workforce planning is especially important in a setting of political, social, and economic uncertainty. Portuguese community pharmacists are experiencing such conditions as well as increasing patient empowerment, shortage of primary care physicians, and primary health care reforms. This study aims to design three future scenarios for Portuguese community pharmacists, recognizing the changing environment as an opportunity to develop the role that community pharmacists may play in the Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Other studies also identified the need for pharmacy consultations to become more patient-oriented. 9,17,22,23 Given the sensitive nature of OEC requests these consultations should be carried in a private area. 24,25 In the present study the SP was not offered this option, although the pharmacy was equipped with a separated seated consultation area.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also identified the need for pharmacy consultations to become more patient-oriented. 9,17,22,23 Given the sensitive nature of OEC requests these consultations should be carried in a private area. 24,25 In the present study the SP was not offered this option, although the pharmacy was equipped with a separated seated consultation area.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise recognized the changing environment as a huge challenge but also an opportunity to develop the role that community pharmacists may play in the Portuguese health system. For this exercise two objectives were considered: (i) to analyze the possible evolution of community pharmacists’ role in the Portuguese healthcare system by building and studying three different scenarios, and (ii) to identify the main driving forces and related uncertainties that may impact on the definition of the future community pharmacists’ role [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Investing in IST and modernizing the architecture of pharmacies is considered as a necessary and critical step towards the diffusion of new forms of practice [22, 23]. eHealth services may develop in the next few years to harvest the full potential of CP, enhancing their role in the primary care network and supporting their activities in chronic disease management [24].…”
Section: Introductionmentioning
confidence: 99%
“…Human Resources for Health (HRH) are widely recognized as the most important assets and the pillar of any health system for the provision, production and delivery of healthcare services [2], thus being one of the focus areas for the strengthening of health policies [3]. …”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) in the 2006 report “Working together for health” identified a global shortage of almost 4.3 million physicians, midwives, nurses and support workers. It also identified the 57 countries with critical shortages of these HRH, 36 of these located in Africa [3]. …”
Section: Introductionmentioning
confidence: 99%